The use of simulation to optimize the pinhole diameter and mask thickness for an x-ray backscatter imaging system - Vella, Anna; Munoz, Andre Arelius Marcus; Healy, Matthew J. F.; Lane, David W.; Lockley, D. (SPIE, 2017)
The PENELOPE Monte Carlo simulation code was used to determine the optimum thickness and aperture diameter of a pinhole mask for X-ray backscatter imaging in a security application. The mask material needs to be thick enough to absorb most X-rays, and the pinhole must be wide enough for sufficient field of view whilst narrow enough for sufficient image spatial resolution. The model consisted of a fixed geometry test object, various masks with and without pinholes, and a 1040 x 1340 pixels’ area detector inside a lead lined camera housing. The photon energy distribution incident upon masks was flat up to selected energy limits. This artificial source was used to avoid the optimisation being specific to any particular X-ray source technology. The pixelated detector was modelled by digitising the surface area represented by the PENELOPE phase space file and integrating the energies of the photons impacting within each pixel; a MATLAB code was written for this. The image contrast, signal to background ratio, spatial resolution, and collimation effect were calculated at the simulated detector as a function of pinhole diameter and various thicknesses of mask made of tungsten, tungsten/epoxy composite or bismuth alloy. A process of elimination was applied to identify suitable masks for a viable X-ray backscattering security application.
Copyright 2017 Society of Photo-Optical Instrumentation Engineers. One print or electronic copy may be made for personal use only. Systematic reproduction and distribution, duplication of any material in this paper for a fee or for commercial purposes, or modification of the content of the paper are prohibited.